Menuntut Tanggung Jawab Hukum IMF - Nandang Sutrisno (Universitas Islam Indonesia, 2003)
The article below discusses the background that the failure of IMF role in overcoming economy crisis of Indonesia. Departing from the failure of IMF program implies other crisis, for instances social and political crisis. According to writer to solve the above problems, alternative solution needs to be solved and the steps that constitutes main way is should be conducted amendment toward IMF Agreement particularly article IX Section 2 (Hi). Section 3 and Section 8 (I) and Guidelines on Conditionality The amendment that makes the government of Indonesia sues IMF based on statutory obligation. Besides, it also needs to be refolmulated a new contract based on contractual obligation, and new international institution to solve debt of developing countries.